Influence of Compensation and Working Condition on Job Satisfaction and Commitment of Lecturers at the College - Muslim Ansori; Christa Caroline (Pusat P2M Politeknik Negeri Batam, 2018)
This study aims to investigated about the influence of compensation and working conditions on job satisfaction and commitment of lecturers at the college. Job satisfaction and commitment of lecturers at the college so need to be considered in carrying out any activities undertaken by the lecturer, without job satisfaction and commitment of the lecturers at the college will lower spirit of lecturers. Respondents in this study is a lecturer of accounting and management, there are 156 lecturers were taken as samples. Techniques determination of the sample using the slovin formula. This study uses a simple linear regression analysis using SPSS 20. The results of this study indicate that the compensation effect on job satisfaction, compensation effect on commitment of lecturers at the college, working condition effect on job satisfaction, and working conditions has no effect the commitment of lecturers at the college.